Comparison of distribution and frequency of impacted teeth before and during COVID-19 pandemic in dental hospital: a descriptive study - Syafin, Haura; Reksoprodjo, Muhammad Ramaditto; Julia, Vera; Heriasti, Maudina Dwi; Ariawan, Dwi; Sulistyani, Lilies Dwi; Utomo, Yudy Ardilla; Ratman, Muhammad Farid (Faculty of Dentistry Universitas Padjadjaran, 2023)
ABSTRACTIntroduction: The occurrence of the COVID-19 pandemic may affect the prevalence of patients with complaints of impacted teeth in dental hospital Faculty of Dentistry University of Indonesia (FKG UI), and there is no recent research on the distribution and frequency of impacted teeth based on age, gender, and teeth type in this hospital during the COVID-19 pandemic. This study aims to determine the distribution and frequency of impacted teeth during the COVID-19 pandemic in dental hospitals. Methods: A descriptive study uses the secondary data on impacted teeth patient's medical records. Utilizing purposive sampling, we selected participants for the research by carefully examining medical records to identify individuals that had undergone impacted tooth removal. The study used secondary data from the medical records of oral surgery patients at dental hospital FKG UI from June 2019 to June 2021, including complete patient identity, clinical diagnosis, and panoramic radiograph of the impacted teeth in June 2019 to June 2021. Diagnosis was determined through screening of medical records and panoramic radiographs. Data were analyzed using the statistical analysis software (SPSS version 21, IBM Corp.) Results: From 3,225 medical records of oral surgery patients at dental hospital FKG UI before and during COVID-19 pandemic, A total of 1292 patients were included in the study and 1496 impacted teeth cases were found. The frequency of impacted teeth cases before the pandemic was 825 (55.1%) cases; there were 671 (44.9%) cases during the pandemic. Conclusion: COVID-19 has caused a decrease in the distribution and frequency of impacted teeth cases, mostly in the middle aged patients, while more female as compared to male. The most common occurrence was in the third molars and the lowest was in the second molar tooth. Keyword : tooth, impacted, COVID-19, retrospective studies, wisdom tooth